Digital Financial Literacy, Behavioral Intention, and Financial Inclusion - Johny Budiman; Candy Candy; Amelia Andita; Errina Ati; Dhamma Vicaya Putri; Larventy Larventy; Michelle Nataline Tu (Universitas Multi Data Palembang, 2026)
This study examines the effects of Digital Financial Literacy (DFL) and Mobile Perceived Financial Cost (MPFC) on Digital Financial Inclusion (DFI), with Behavioral Intention (BI) and Use behavior (UB) as mediating variables. Using a quantitative approach, data were collected from 203 mobile fintech users in Batam City and analyzed with PLS-SEM. The results show that DFL has a positive and significant effect on BI, which subsequently influences UB and enhances DFI. BI and UB act as mediating variables, while MPFC has no significant effect on fintech usage. These findings emphasize the importance of digital financial literacy in promoting digital financial inclusion.